1994
DOI: 10.1093/humrep/9.suppl_1.77
|View full text |Cite
|
Sign up to set email alerts
|

Non-competitive anti-oestrogenic activity of progesterone antagonists in primate models

Abstract: We have summarized some of the studies containing basic biological data suggesting potential therapeutic utility of the anti-proliferative activity of antiprogestins on uterine tissues. The non-competitive anti-oestrogenic effects of RU486 were examined using oestradiol-treated ovariectomized monkeys given RU486, progesterone or both. The oestradiol-induced luteinizing hormone surge of control animals was abrogated by progesterone and/or RU486. Secretory transformation by progesterone was inhibited by RU486 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Studies in knockout mice and by pharmacological modulation in nonhuman primates have revealed a direct role for the progesterone receptor in ovarian function and endometrial growth (Conneely et al, 2001;Slayden et al, 2001a;Brenner et al, 2010), suppressing the proliferative effects of estrogen on the endometrium (Wolf et al, 1989;Hodgen et al, 1994;Slayden and Brenner, 2004;Slayden et al, 2006;Brenner et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in knockout mice and by pharmacological modulation in nonhuman primates have revealed a direct role for the progesterone receptor in ovarian function and endometrial growth (Conneely et al, 2001;Slayden et al, 2001a;Brenner et al, 2010), suppressing the proliferative effects of estrogen on the endometrium (Wolf et al, 1989;Hodgen et al, 1994;Slayden and Brenner, 2004;Slayden et al, 2006;Brenner et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…RU-486 is a different type II P4 receptor antagonist with higher antiglucocorticoid activity than ORG (50,51). These effects of RU-486 resemble its blockade of the P4-dependent dendritic loss after proestrus (1).…”
Section: P4-e2 Antagonism Of Neurite Outgrowth Is Mediated By P4 Recementioning
confidence: 99%
“…Mifepristone and other PR antagonists have been shown to exert an antiproliferative effect on the endometrium of nonhuman primates (10,11) and women (12,13) and in Ishikawa endometrial adenocarcinoma cells (14). Data also suggest that the endometrial androgen receptor (AR) may play an important role in these effects (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%